Corporate Social Responsibility Activities and Green Innovation Performance in Organizations: Do Managerial Environmental Concerns and Green Absorptive Capacity Matter? - Mo, Xiaoping; Boadu, Francis; Liu, Yunqing; Chen, Zhen; Ofori, Adwoa Serwaa (Frontiers in Psychology, 2022)
From the environmental sustainability perspective, scholars have considered corporate social responsibility activities as an essential mechanism for enhancing enterprise performance and innovation outcomes. However, how and under what conditions corporate social responsibility activities influence green innovation performance in emerging economies is still unclear. From the perspective of the theory of planned behavior, we construct a theoretical model to assess how corporate social responsibility activities affect enterprises’ green innovation performance. Explicitly, we investigate the mediating and moderating effects of managerial environmental concern and green absorptive capacity on the relationship between corporate social responsibility activities and enterprises’ green innovation performance. This research relies on a sample of 358 enterprises from the manufacturing and service sectors in China, and uses regression analysis and bootstrap to test the hypotheses proposed. The empirical results demonstrate that (1) Corporate social responsibility activities positively enhance enterprises’ green innovation performance; (2) Corporate social responsibility activities have a positive influence on managerial environmental concern; (3) Managerial environmental concern has a mediating role between corporate social responsibility activities and green innovation performance; (4) Managerial environmental concern has a powerful influence on green innovation performance; (5) Green absorptive capacity positively moderates the association between managerial environmental concern and green innovation performance. This research work proposes that managerial environmental concern and green absorptive capacity play a mediating and moderating function on the linkage amongst corporate social responsibility activities and green innovation performance.